DEVELOPMENT AND VALIDATION OF HPLC METHOD FOR THE DETERMINATION OF RESVERATROL IN BULK DOSAGE FORM, COMMERCIAL TABLET, AND MULTIWALLED CARBON NANOTUBES-BASED FORMULATION - SHARMA, NEHA; MISHRA, YACHANA; SHARMA, NEELAM; MISHRA, VIJAY (International Journal of Applied Pharmaceutics, 2025)
Objective: Resveratrol (RES), a polyphenol, is a promising option to treat multiple diseases due to its anticancer, cardioprotective, anti-inflammatory, and antioxidant activities. The present study was designed to develop and validate a simple, precise, rapid and reproducible analytical method for the detection of RES in different formulations. Methods: A novel analytical technique was developed and validated for the detection of RES via ultrafast liquid chromatography utilizing C18 column. Methanol along with high-performance liquid chromatography (HPLC) grade water (40:60) was used as a mobile phase with a rate of flow of 0.8 ml/min. This technique has been validated following the International Conference for Harmonization (ICH) Q2 (R1) guidelines. The method's accuracy was determined through the percent recovery within the limit of 95 to 105%. Results: The method demonstrated linearity within the 2-10 µg/ml range, exhibiting a regression coefficient of 0.997. The precision of the method was indicated by the percentage RSD, which was recorded to be less than 2%. Limit of detection (LOD), and limit of quantification (LOQ) were found to be 1.6 µg/ml and 4.8 µg/ml, respectively. The proposed approach has been proved to be robust because the response did not significantly change due to a change in the rate of flow, along with the composition of the mobile phase. Conclusion: The results of the study demonstrated that the developed method has passed all the validation test parameters and can be applied for the estimation of RES in bulk dosage form, commercial tablet, and developed multiwalled carbon nanotube (MWCNTs)-based formulations.